Towards the integrated management of Fusarium wilt of banana - Blomme, Guy; Mahuku, George; Kearsley, Elizabeth; Dita, Miguel (MDPI, 2024)
This Special Issue contains a selection of papers dealing with Fusarium wilt of banana (FWB), with a special focus on the Fusarium strain Tropical Race 4 (TR4), and explores (1) options for effective integrated management strategies, (2) the detection and development of disease-resistant cultivars, and (3) the distribution and diversity of the pathogen [...]